2020
DOI: 10.18004/rspp.2020.diciembre.50
|View full text |Cite
|
Sign up to set email alerts
|

Factors that facilitate or hinder the Continuity of Care in the Service Network of the Presidente Hayes Department according to attributes of the RIISS, Paraguay, 2018-2019

Abstract: Introducción: El estudio se desarrolla en el Departamento de Presidente Hayes XV Región Sanitaria dependiente del Ministerio de Salud Pública, en un área rural caracterizada por fragilidades de comunicación, disponibilidad de recursos y débiles procesos de capacitación. Objetivo: Evaluar factores que facilitan o dificultan la la Continuidad del Cuidado en la Red de Servicios del Departamento de Presidente Hayes según atributos de las RIISS, Paraguay durante los años 2018 a 2019. Metodología: Estudio observacio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…Among the main weaknesses, a lack of human and financial resources has been observed, along with the weak governance of public organizations [ 15 ]. Furthermore, through interviews with key actors, Villalba, B., et al [ 73 ] identified a need to increase the level of qualification among professionals.…”
Section: The Latin American Experience In Phc and Health Networkmentioning
confidence: 99%
“…Among the main weaknesses, a lack of human and financial resources has been observed, along with the weak governance of public organizations [ 15 ]. Furthermore, through interviews with key actors, Villalba, B., et al [ 73 ] identified a need to increase the level of qualification among professionals.…”
Section: The Latin American Experience In Phc and Health Networkmentioning
confidence: 99%